RETRACTED: Klotho Gene and Protein in Human Placentas According to Birth Weight and Gestational Age - Iñiguez, Germán; Gallardo, Pedro; Castro, Juan Jose; Gonzalez, Rene; Garcia, Mirna; Kakarieka, Elena; San Martin, Sebastian; Johnson, Maria Cecilia; Mericq, Verónica; Cassorla, Fernando (Frontiers in Endocrinology, 2019)
Introduction: Fetal growth restriction may be the consequence of maternal, fetal, or placental factors. The insulin-like growth factors (IGFs) are major determinants of fetal growth, and are expressed in the mother, fetus and placenta in most species. Previously we reported higher placental protein content of IGF-I, IGF-IR and AKT in small (SGA) compared with those from appropriate for gestational age (AGA) placentas. The protein Klotho, has been reported in placenta and may regulate IGF-I activity. In this study we determined Klotho gene expression and protein immunostaining in term (T-SGA y T-AGA) and preterm (PT-SGA y PT-AGA) human placentas. In addition, we assessed the effect of Klotho on the IGF-IR and AKT activation induced by IGF-I. Methods: Placentas (n=117) from 32 T-SGA (birth weight (BW) = -1.74 ± 0.08 SDS), 37 T-AGA (BW= 0.12 ± 0.12 SDS) , 20 PT-SGA (BW= -2.08 ± 0.14 SDS),and 28 PT-AGA (BW= -0.43 ± 0.13 SDS) newborns were collected. mRNA expression by RT-PCR in the chorionic (CP) and basal (BP) plates of the placentas, and the presence of Klotho was evaluated by immunohistochemistry (integral optical density, IOD). In addition, we developed placental explants that were incubated with IGF-I in the presence or absence of Klotho. Results: We found a lower mRNA expression and protein immunoreactivity of Klotho in the CP of SGA (term and preterm) compared with AGA placentas. We also observed a significant reduction in IGF-IR tyrosine activation induced by IGF-I 10 nM when preincubated with 2.0 nM of Klotho (2.4±0.5 arbitrary units vs 1.3±0.3 AU) , and similar results we observed on AKT and ERK42/44 activation Conclusion: We describe for the first time that Klotho mRNA and protein varies according to fetal growth and gestational age. In addition, Klotho appears to down-regulate the activation induced by IGF-I on IGF-IR and AKT, suggesting that Klotho may be regulating IGF-I activity in human placentas according to intrauterine fetal growth.